Knowledge, socio demographic profile, vaccination status and factors determining the acceptance of hepatitis B vaccine among nursing staff of KPC Medical College of West Bengal - Sikder, Rajib; Kundu, Subha Sankha; Dey, Rituraj; Pattanayak, Ujjwal; Majumdar, Kunal Kanti; Joardar, Gautam Kumar (International Journal Of Community Medicine And Public Health, 2020)
Background: Hepatitis B, a vaccine preventable infection is one of the important causes of morbidity in India. The risk of acquiring the infection is more among the health care providers like nurses than in general population as they come in close contact with patients. The study has been done to know the sociodemographic profile, vaccination status along with the knowledge about the disease and the factors determining the acceptance of vaccination among nursing staff of KPC Medical College in West Bengal. Methods: A cross-sectional study was carried out among the 284 nursing staff of KPC Medical College and Hospital in November to December, 2018 with the help of pre-designed and semi-structured questionnaire. Data on demographic characteristics, knowledge, occupational exposure, vaccination status and factors for acceptance of vaccine etc. were collected and analysed. Results: 86% nursing staff received vaccination out of which 71% were completely vaccinated, 29% were partially and 14% were non vaccinated. The acceptable knowledge was found in 84% of the nurses. The major reason of vaccination was to protect themselves from infection and the major reason for non-acceptance was time limitation, cost issues etc. Accidental prick was found in 5% of the nurses and universal precautionary measure was taken by 98% of the nurses. Conclusions: In spite of availability of safe, effective and cheap vaccine against hepatitis B infection, 29% of nursing staff were partially vaccinated and 14% were non-vaccinated. There should be a mandatory vaccination at the beginning of their training and frequent educational and awareness programme for them on hepatitis B.